Gross Motor and Social Development of Children Development Media of Traditional Jumping Rope Modification Game - Nissa, Heppy Zakiatun; Mustaji, Mustaji; Hendratno, Hendratno (Universitas Malikussaleh, 2020)
The purpose of this research is to know the validity, practicality and effectiveness of media traditional jumping rope modification game to improve the development of gross motor and social of children. The research method used Dick and Carey model development research with the following steps: a). Analyzing the need, b.) Analyzing learning, c.) Analyzing child characteristics and learning context, d.) Formulating specific learning objectives, e.) Develop research instruments, f.) Develop learning strategies, g.) Develop teaching materials, h.) Designing and implementing formative evaluation, i.) Revising learning. The subject of research taken is kindergarten children aged 5-6 years as much as 54 children. The subject of research also involves 2 material experts and media experts. Data collection using a product feasibility test poll from media experts and material experts, interviews on individual trials, interviews on small group trials and observation sheets on field trials with indicators on gross motor development, among others, coordinated body movements to train flexibility, balance and agility, jump over obstacles with a height of 20-40 cm, and perform a leap of 38-60 cm towards the target with obstacles. As for indicators of social development, among others, obey the rules of the game, play with peers, be cooperative with friends, and realize the rights and interests of others. Data analysis techniques using the N-Gain Score index. Development research resulted the product of the Game media usage Guide Book of